Captopril challenge test in the diagnosis of primary aldosteronism: consistency between 1- and 2- h sampling - Liu, Xinyu; Guo, Chao; Bian, Jin; Hao, Sufang; Lou, Ying; Zhang, Huimin; Zhou, Xianliang; Cai, Jun; Ma, Wenjun (Frontiers in Endocrinology, 2023)
Objective: To examine the consistency of plasma aldosterone concentration at 1 and 2 h in captopril challenge test (CCT), and to explore the possibility of replacing 2-h aldosterone concentration with 1-h aldosterone concentration for diagnosis of primary aldosteronism (PA). Methods: This retrospective analysis included a total of 204 hypertensive patients suspected of having PA. Subjects received oral captopril challenge at 50 mg (25 mg if the systolic blood pressure was <120 mmHg), and plasma aldosterone concentration and direct renin concentration were measured at 1 and 2 h afterward (chemiluminescence immunoassay Liaison DiaSorin, Italy). Sensitivity and specificity were used to reflect the diagnostic performance of 1-h aldosterone concentration using 2-h aldosterone concentration (11 ng/dL as the cutoff) as the reference. A receiver operating characteristic curve analysis was also conducted. Results: Among the 204 included patients [median age of 57.0 (48.0-61.0) years, 54.4% male], a diagnosis of PA was established in 94 patients. Aldosterone concentration in the patients with essential hypertension was 8.40 (interquartile range 7.05-11.00) ng/dL at 1 h and 7.65 (5.98-9.30) ng/dL at 2 h (P < 0.001). In patients with PA, aldosterone concentration was 16.80 (12.58-20.50) ng/dL at 1 h and 15.55 (12.60-20.85) ng/dL at 2 h (P > 0.999). At a cutoff of 11 ng/dL, the sensitivity and specificity of using 1-h aldosterone concentration to diagnose PA were 87.2% and 78.2%, respectively. A higher cutoff of 12.5 ng/mL increased specificity to 90.0% but decreased sensitivity to 75.5%. A lower cutoff of 9.3 ng/mL increased sensitivity to 97.9% but decreased specificity to 65.4%. Conclusions: When diagnosing PA with CCT, 1-h aldosterone concentration could not be used to replace 2-h aldosterone concentration.